Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s40813-016-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings on the effect of the pig appeasing pheromone in a slow releasing block on the welfare of pigs at weaning

Abstract: The pig appeasing pheromone (PAP) applied in spray has shown to be effective in reducing the frequency of aggression and the stress response of young and adult pigs under experimental conditions. This preliminary experiment investigates the effect of the PAP in a slow releasing block on the behaviour and skin lesions of weaners after mixing on a commercial farm. Two identical rooms containing six replicates per treatment of a commercial weaner building were used. There were two treatments (PAP block and Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
(13 reference statements)
1
16
0
Order By: Relevance
“…It has, therefore, been suggested that simply placing a heat source in the creep area does not effectively entice piglets away from the sow when not nursing [ 34 ]. It was, therefore, hypothesised that the use of a heat mat with the addition of the SOA, being a synthetic analogue of pheromones and known to be an attractant for nursing piglets [ 15 , 16 ], would attract more piglets to the creep area and, thus, reduce mortality. In fact, the number of piglets lying next to the sow’s udder in the 10-min intervals was increased in SOA treated crates and inversely the number of piglets in the control treatment spent more time in the creep area, although this was also dependent on the time of day.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has, therefore, been suggested that simply placing a heat source in the creep area does not effectively entice piglets away from the sow when not nursing [ 34 ]. It was, therefore, hypothesised that the use of a heat mat with the addition of the SOA, being a synthetic analogue of pheromones and known to be an attractant for nursing piglets [ 15 , 16 ], would attract more piglets to the creep area and, thus, reduce mortality. In fact, the number of piglets lying next to the sow’s udder in the 10-min intervals was increased in SOA treated crates and inversely the number of piglets in the control treatment spent more time in the creep area, although this was also dependent on the time of day.…”
Section: Discussionmentioning
confidence: 99%
“…The placement of the SOA diffuser block can be seen in Figure 1 . The active components of the SOA block were based on mammary secretions of the sow and included: methyl caprate, methyl laurate, methyl miristate, methyl palmitate, methyl linoleate, methyl oleate [ 15 ]. Given the fact the SOA treatment was an air diffuser, all SOA treated sows were confined to one room in the first replicate and Control to another.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the implementation of these new practices could be challenging for the stakeholders. An alternative to reduce the impact of the stress could be the use in young animals of appeasing pheromones, as demonstrated in several species [19][20][21]. The production of these hormones during nursing exists in all mammals including bovine.…”
Section: Introductionmentioning
confidence: 99%